The Motivation of the Officials in the Local Administration in Bulgaria - Problems and Possible Solutions - Boianov, Kalin (Research Papers, 2018)
In any organization, whether large or small, employees work enthusiastically or with jealousy, cooperate with each other and with the management to achieve the set goals. The relationship between motivation and local government employees is a neglected topic of research in Bulgaria. Therefore, this article attempts to explore the types of motivations that local government employees need to gain, and the extent to which the lack of motivational impact affects the spirit of employees in fulfilling the organization’s defined goals, mission and vision.